Dynamic Quantitative Trait Loci Mapping for Plant Height in Recombinant Inbred Line Population of Upland Cotton - Wu, Jing; Mao, Lili; Tao, Jincai; Wang, Xiuxiu; Zhang, Haijun; Xin, Ming; Shang, Yongqi; Zhang, Yanan; Zhang, Guihua; Zhao, Zhongting; Wang, Yiming; Cui, Mingshuo; et al. (Frontiers in Plant Science, 2022)
Plant height (PH) is a key plant architecture trait for improving the biological productivity of cotton. Ideal PH of cotton is conducive to lodging resistance and mechanized harvesting. In order to detect quantitative trait loci (QTL) and candidate genes of PH in cotton, a genetic map was constructed with a recombinant inbred line (RIL) population of upland cotton. PH phenotype data under 9 environments and 3 best linear unbiased predictions (BLUPs) were used for QTL analyses. Based on restriction-site associated DNA sequence (RAD-seq), the genetic map contained 5850 single-nucleotide polymorphism (SNP) markers, covering 2747.12 cM with an average genetic distance of 0.47 cM. Thirty-seven unconditional QTLs explaining 1.03% to 12.50% of phenotypic variance, including 4 major QTLs and 7 stable QTLs, were identified. Twenty-eight conditional QTLs explaining 3.27% to 28.87% of phenotypic variance, including 1 major QTL, were identified. Importantly, five QTLs, including 4 stable QTLs, were both unconditional and conditional QTL. Among the 60 PH QTLs (including 39 newly identified), none of them were involved in the whole period of PH growth, indicating that QTLs related to cotton PH development have dynamic expression characteristics. Based on the functional annotation of Arabidopsis homologous genes and transcriptome data of upland cotton TM-1, 14 candidate genes were identified within 10 QTLs. Our research provides valuable information for understanding the genetic mechanism of PH development, which also increase the economic production of cotton.